Dermatoscopic findings of penile intraepithelial neoplasia: Bowenoid papulosis, Bowen disease and erythroplasia of Queyrat. (25th December 2018) - Chan, Su‐Lin; Watchorn, Richard Edward; Panagou, Evangelia; Panou, Evdoxia; Ong, Eugene LH; Heelan, Kara; Haider, Aiman; Freeman, Alex; Bunker, Christopher Barry
Abstract: Background/Objectives: The clinical diagnosis of penile intraepithelial neoplasia is challenging. No specific dermoscopic criteria for penile intraepithelial neoplasia have been described in the literature. This study aimed to describe and evaluate the dermoscopic features of penile intraepithelial neoplasia. Methods: Clinical and dermoscopic images of 11 patients with histopathologically confirmed penile intraepithelial neoplasia were recorded and evaluated. Results: The most frequent dermoscopic features were the presence of structureless areas (100%, structureless pink 72.7%) and vascular structures (81.8%), particularly dotted vessels (72.7%). Other findings included the absence of a pigment network (100%); scale (45.5%); scar‐like areas (45.5%); erosions (27.3%); and pigmentation consisting of brown‐grey dots and globules (27.3%). Conclusions: The dermoscopic features that characterise penile intraepithelial neoplasia are structureless pink areas and a prominent vascular pattern (mainly clustered dotted vessels). Dermoscopy is a useful tool that can aid in the diagnosis and surveillance of penile intraepithelial neoplasia.